PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA DELUXE DUO LAUNDRY DI KOTA BUKITTINGGI - Rika Novita Sari (STIE Perbankan Indonesia, 2019)
This study aims to analyze the Effect of Service Quality on Consumer Satisfaction in Deluxe Duo Laundry in the City of Bukittinggi, from the results of research that I found in the field using the population in this study all consumers at the Bukittinggi Duo Laundry Deluxe amounting to 400 people, samples from this study get from the results using the Slovin formula as many as 80 people. From the results of the data obtained from the respondents processed by using the SPSS program with the stages through the research instrument test, namely the test of validity, reliability, descriptive of respondents, to logistics binary regression analysis. From the results of the logistic binary regression analysis, the authors found that of the five independent variables the authors examined, namely physical evidence, reliability, responsiveness, assurance and empathy had a positive and significant influence on Consumer Satisfaction in the Bukittinggi Deluxe Duo Laundry. Then seen from the results of the G test shows that service quality variables consisting of physical evidence, reliability, responsiveness, assurance and empathy simultaneously have a positive and significant influence on Consumer Satisfaction in Bukittinggi Deluxe Duo Laundry. The results of the B expectations test show that the most dominant variable influencing Consumer Satisfaction in Bukittinggi's Deluxe Duo Laundry is the reliability variable.